Thermal modelling of ultrarelativistic heavy ion collisions conserving strangeness exactly - Marais, Mark (Department of Physics, 2024)
[ pg 56-60,87,88 missing] Thermal modelling of particle production in ultrarelativistic heavy ion collisions incorporating appropriate conservation principles with respect to the relevant quantum numbers, has been highly successful in determining chemical freeze-out conditions across a wide range of beam energies. This is done for heavy-ion collisions in the broad range of energy from SIS/GSI through AGS/BNL up to BPS/CERN and RHIC/BNL, assuming that particles can be described by a hadron gas in thermal and chemical equilibrium. The role of strangeness conservation and strangeness equilibration is a central feature in our considerations. Fits to the data from collaborations at the above facilities, and, comparisons with analysis done by other authors, are made. Energy dependence of the chemical freeze-out parameters is studied and, recently proposed criteria for freeze-out in terms of energy per particle and total baryon density are investigated. The chemical freeze-out trajectory is compared with the phase boundary between the hadron gas phase and the quark-gluon plasma in the temperature versus baryochemical potential plane.